Dialectical relationship between religious texts and social reality in the philosophy of da’wa - Asror, Ahidul (Penerbit Universiti Kebangsaan Malaysia, 2020)
This paper criticizes the thinking way in the development of the da’wa science which initially focuses on the religious texts. The development of the da’wa science with this method has implications for the birth of the theory that emphasizes deductive patterns. The flow of deductive thinking makes the Qur’an and sunnah more functions to subdue the ratio that should be critical to the social situation. The epistemology of science is considered to have several weaknesses, where religious texts and social reality are placed in dichotomous patterns of relationships. This situation makes the da’wa science unable to present as knowledge that is able to respond to contemporary problems. In the next period, the da’wa method changes and tends to choose how it works. Like social science, da’wa focuses more on the empirical reality study. As part of the Islamic science, da’wa faces problems when it is understood only as a study of social behavior. This paper offers a dialectical method of seeing the problems faced by the da’wa science. The critical reconstruction in building da’wa science by utilizing dialectical methods is carried out so that da’wa can consider religious texts and social reality as sources of knowledge. The application of this dialectical method provides a conclusion in the form of a shift in the da’wa paradigm, from the dichotomous into an integrative and humanist style of science. This dialectical reasoning positions the da’wa science as a scientific discipline in Islamic studies so that it is able to touch the social life.